The perception of Kota Kinabalu employers towards minimum wage policy / Aidil Izan Hinjam and Dalilah Rosdin - Hinjam, Aidil Izan; Rosdin, Dalilah (2013)
Poverty is the issue that all nations faced and unavoidable forces that need to be face by any government and countries. Every nations need to come up with their own initiatives or use their own strategies on how to handle poverty issue in their own nation as every nation have different kind of poverty problem. Malaysia government had introduced many policies that can help to reduce the rate of poverty in this country and overall the policies that have been implement shows the rate of poverty is decreasing. However. there is still some vulnerable group of society that still facing and having income below poverty line income due to the some geographical and societal reasons. According to National Consultative council (NWCC) in its research title "Minimum wage policy - Curse or cure" poverty line income in peninsular, Sabah and Sarawak are RM 763, RM 1048 and RM 912 respectively in 2 009. Poverty nowadays is much more difficult to handle, as it is depends on how far the government itself had done to solve it as it is not a simple matter that can be handle just like that. To handle such problem, government need to come up with many initiatives and the boldest one is minimum wage policy. Minimum wages policy is a policy implemented by Malaysian government in determining the lowest pay rates for labor forces in Malaysia. According to International Labor Organization (ILO), minimum wages is "the lowest level of remuneration permitted ... which in each country has the force of law and which is enforceable under threat of penal or others appropriate sanction". This means that, minimum wages is a collective agreement between the employer with the government that binding the employer to pay the lowest amount of salary to their employees accordance to the policy. The implementation of minimum wage in Malaysia started on 1 January 2013 after being gazette on 15 September 2 011. As recommended by National Wage Consultative Council (NWCC) and implemented by the government, Malaysian labor market will have a set of fixed salary that is RM 800 for Sabah, Sarawak and Labuan and RM 900 for peninsular Malaysia. To determine the fairness and to be able to defense their own idea, our government and National Wages Consultative Council (NWCC) had come up with one method to justify the differences in the minimum wages policy between Peninsular with Sabah, Labuan and Sarawak. According to National Consultative Council (2012), the daily rates of employee's salary measured by or calculated based on the following formula on their wages rate where rate of monthly minimum wage multiple by twelve months and then divided by fifty two weeks multiple number of working days in a week.